Syndecan-1 as a predictor of vulnerable atherosclerotic plaques - Qiu, Yan; Ouyang, Zhi; Zhong, Jian; Jin, Linlu; Qin, Yixue; Zeng, Ye (Frontiers in Cell and Developmental Biology, 2024)
This study highlights the significance of syndecan-1 in plaque vulnerability and provides valuable insights into the formation of high-risk vulnerable plaques in atherosclerosis. These findings have substantial implications for cardiovascular disease management, as early identification of vulnerable plaques can lead to timely interventions and prevent life-threatening events. Moreover, the exploration of syndecan-1 as a biomarker offers a promising tool for risk stratification and personalized treatment approaches.